2019
DOI: 10.1038/s41598-018-36529-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cellulose synthase-like D (CSLD) family revealed the involvement of PtrCslD5 in root hair formation in Populus trichocarpa

Abstract: Cellulose synthase-like D (CSLD) family was characterized for their expression and functions in Populus trichocarpa. Ten members, PtrCslD1-10, were identified in the P. trichocarpa genome, and they belong to 4 clades by phylogenetic tree analysis. qRT-PCR and promoter:GUS assays in Arabidopsis and P. trichocarpa displayed divergent expression patterns of these 10 PtrCSLD genes in root hairs, root tips, leaves, vascular tissues, xylem and flowers. Among PtrCslD2, PtrCslD4, PtrCslD5, PtrCslD6, and PtrCslD8 that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 53 publications
(93 reference statements)
2
15
0
Order By: Relevance
“…The plant cell wall consists of polysaccharides (cellulose, hemicellulose and pectin), proteins and other compounds. It plays critical roles in the maintenance of cell integrity, and the regulation of many developmental processes in plants [ 1 , 2 , 3 , 4 , 5 , 6 ]. The cell wall represents not only a mechanical barrier, but also a signaling component during plant responses to various biotic [ 7 , 8 ] and abiotic stresses [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant cell wall consists of polysaccharides (cellulose, hemicellulose and pectin), proteins and other compounds. It plays critical roles in the maintenance of cell integrity, and the regulation of many developmental processes in plants [ 1 , 2 , 3 , 4 , 5 , 6 ]. The cell wall represents not only a mechanical barrier, but also a signaling component during plant responses to various biotic [ 7 , 8 ] and abiotic stresses [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant Csl genes play substantial roles in developmental processes, such as root hair formation [ 6 ], the control of organ size [ 4 ], tiller number [ 3 ] and the maintenance of adherent mucilage structure [ 1 , 2 , 5 ]. Csl genes were also reported to be involved in plant resistance/tolerance to biotic or abiotic stresses, such as salt [ 35 , 36 ], boron (B) [ 37 , 38 ] or heavy metal [ 36 , 39 ] stress, as well as pathogen infection [ 32 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…To find out if our discoveries could be applied to other species, we performed a cross-species complementation experiment which showed that AtCSLD2 and AtCSLD3 (KOJAK), required for root hair development in Arabidopsis (Bernal et al, 2008), are functionally equivalent to LjCSLD1. In Populus trichocarpa PtrCslD5 is considered a functional orthologue of AtCLSD3 and along with the highly homologous PtrCslD6, it is also involved in root hair development (Peng et al, 2019). Similarly, rice OsCSLD1 is also required for root hair morphogenesis (Kim et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DcCslD5 was in clade III as well as functions of OsCslD4, PtrCslD2 and AtCslD5 were studied, which mutants displayed educe stem growth and synthesis of polysaccharides [49,50]. In clade IV, AtCslD6, PtrCslD3, PtrCslD4 and PAXXG254610 shared the same lineage; none of those were identified for their functions [33]. Based on the phylogenetic tree analysis, DcCslD2a, DcCslD2b, DcCslD3a and…”
Section: Phylogenetic Analysis and Classification Of Csld Proteins Inmentioning
confidence: 99%
“…It is conserved in all land plants, and among the ten Csl subfamilies, it shows the highest sequence similarity to the cellulose synthase genes, suggesting that it plays fundamental roles in plant development [25,26]. Many studies have described that CslDs are involved in various aspects of the plant life cycle, including synthesis of polysaccharides [27][28][29], environmental stimuli response [30], the expansion and division of cells [31][32][33], plant development [34][35][36][37] and so on. Over the past few years, the CslD family genes have been identified from the genome of various species, such as Arabidopsis thaliana [17,32], Populus trichocarpa [38], Zea mays L [31], Dendrobium catenatum [28,29],…”
Section: Introductionmentioning
confidence: 99%